Identification of a novel galectin in Sinonovacula constricta and its role in recognition of Gram-negative bacteria. Issue 80 (September 2018) - Bai, Yuqi; Niu, Donghong; Bai, Yulin; Li, Yan; Lan, Tianyi; Peng, Maoxiao; Dong, Zhiguo; Li, Jiale
Abstract: Galectins are soluble lectins that perform a pattern recognition function in invertebrate immunity and specifically recognise β-galactoside residues via conserved carbohydrate recognition domains. However, their function in bivalve molluscs has received little attention. Herein, a galectin (ScGal2) in razor clam ( Sinonovacula constricta ) consisting of a 507 bp open reading frame encoding a protein of 168 amino acids was identified and characterised. The protein includes a carbohydrate recognition domain (CRD), and several residues involved in dimerisation were found. ScGal2 mRNAs were mainly detected in hemolymph and liver, and expression was upregulated significantly following challenge with Vibrio anguillarum . Recombinant rScGal2 protein displayed strong agglutination activity toward Gram-negative bacteria, and flow cytometry revealed that ScGal2 strongly promoted phagocytosis in hemocytes. These results suggest that ScGal2 plays an indispensable role in innate immunity in razor clam, and likely participates in immune recognition and clearance processes. Highlights: Galectin ScGal2 from razor clam was identified and characterised. ScGal2 mRNA is expressed in all tissues, and most strongly in hemolymph and liver. ScGal2 is up-regulated following challenge with Vibrio anguillarum . ScGal2 agglutinates Gram-negative bacteria and promotes phagocytosis in hemocytes. ScGal2 participates in immune recognition and clearance processes in razor clam.